Experimental realization of Bloch oscillations in a parity-time synthetic silicon photonic lattice - Ye-Long Xu (Nature Portfolio, 2016)
Bloch oscillations are a fundamental electron transport phenomenon in condensed matter. Here, the authors experimentally realize spatial Bloch oscillations in a non-Hermitian integrated photonic system using CMOS compatible fabrication processes, contributing to improving the understanding of non-Hermitian transport phenomena.